ChemInform Abstract: Flow Heck Reactions Using Extremely Low Loadings of Phosphine‐Free Palladium Acetate. Issue 5 (4th February 2014) - Cyr, Patrick; Deng, Stella T.; Hawkins, Joel M.; Price, Kristin E.
Abstract The reactions are run in a mesoscale flow reactor which allows precise control of reaction times and temperatures.